a Upaya Meningkatkan Pemahaman Materi Sumber Daya Alam Melalui Metode Demontrasi Pada Siswa Kelas VII MTs Mambaul Ulum: Upaya Meningkatkan Pemahaman Materi Sumber Daya Alam Melalui Metode Demontrasi Pada Siswa Kelas VII MTs Mambaul Ulum - nabiil afiyah, khairunnisa (Maliki Interdisciplinary Journal, 2025)
This study aims to improve students' understanding of Natural Resources material through the application of the demonstration method in class VII MTs Mambaul Ulum. The background of this study is the low student learning outcomes caused by conventional learning methods that do not involve student activeness. This research uses a qualitative approach in the form of Classroom Action Research (PTK) with data collection techniques through observation, interviews, and documentation. The results showed that the application of the demonstration method significantly improved students' understanding of the concept of Natural Resources. Students become more active, enthusiastic, and easy to understand the material because they can directly see examples or processes that are explained. Interviews with students and teachers also showed a positive response to this method. Thus, the demonstration method is proven to be effective in improving the quality of learning and student learning outcomes on Natural Resources material.